Holocrine Poroma: A Distinctive Adnexal Tumor. (June 2018) - Horenstein, Marcelo G.; Sandoval, Marina P.; Lo, Yungtai; Jacob, Jack
Abstract : Abstract: There are 36 cases of complex poroid tumors with folliculosebaceous and apocrine differentiation reported in the literature. The authors evaluated 111 poroid tumors including 63 typical eccrine poromas and 48 poroid tumors with folliculosebaceous elements. Folliculosebaceous poroid tumors (FSPT) had basaloid and squamous cells (100%), ducts with steatocystoma-like cuticles and holocrine secretions (89.6%), infundibular follicular structures (66.7%), and entrapped sebocytes (56.3%). No definite apocrine decapitation secretions in FSPT were found. Immunohistochemistry was strongly positive for CK903 and focally positive for CAM5.2, epithelial membrane antigen, and carcinoembryonic antigen. No loss of MLH-1, MSH-2, or MSH-6 mismatch repair proteins was found. FSPT had distinctive features that differentiate them from eccrine poromas including the frequent head and neck locations (62.5% vs. 20.6%, P < 0.01), squamous cytology (100% vs. 1.6%, P < 0.01), more prominent cytoplasmic vacuolization (score 1.4/4.0 vs. 0.3/4.0, P < 0.01), presence of infundibular follicular structures (score 1.2/4.0 vs. 0.03/4.0, P < 0.01), presence of ducts with steatocystoma-like cuticles (89.6% vs. 0.0%, P < 0.01), and less stromal hyalinization (score 1.0/4.0 vs. 2.5/4.0, P < 0.01). The authors propose that FSPT are distinctive benign tumors originating from the sebaceous gland duct and are therefore best categorized as holocrine poroma.